Histiocytosis masquerading in the mesentery and pleura. Issue 11 (1st December 2019) - Dhillon, Nina; Skinnider, Brian; Darabian, Saman; Carruthers, Mollie
Abstract : We present an atypical presentation of Rosai-Dorfman disease (RDD). Due to its overlap with IgG4-related disease (IgG4-RD), this case proved to be a diagnostic dilemma. Our case is an example of the importance of having a broad-based differential and, ultimately, an in-depth histopathological review. Our patient presented with a constellation of symptoms suggestive of an underlying malignancy. He was provisionally diagnosed with peritoneal carcinomatosis of an unknown primary. His initial presentation triggered a series of investigations, surgery and biopsies. Omental biopsy specimens were suggestive of IgG4-RD. Despite appropriate treatment for IgG4-RD, his disease progressed, specifically in the lungs. Pleural biopsies were then collected and assessed alongside the omental biopsies. On review and reassessment, the patient was formally diagnosed with RDD.